Reduction of DBP precursors and their THMFPs in leachate contaminated groundwater by PAC adsorption - Kanlayanee Yimyam (2018)
© 2017 Chulalongkorn University 1. All rights reserved. This research investigated the reduction of dissolved organic matter (DOM) fractions and their trihalomethane formation potentials (THMFPs) by powder activated carbon (PAC) adsorption. Leachate contaminated groundwater around an inactive open-dumping landfill was selected as the raw water. The PAC adsorption reaction was proven to be the pseudo second order kinetic reaction and the Freundlich isotherm. The dissolved organic carbon (DOC), dissolved organic nitrogen (DON), and THMFP removals were 55%, 57%, and 73%, respectively. The hydrophobic (HPO) fraction exhibited a higher THMFP compared to the hydrophilic (HPI) fraction. The results of DOM fractionation show that the use of PAC adsorption produced an efficient 87% reduction of the HPO fraction, which is characterized as having a high reactivity toward THMFP.